Integrated Sensing and Communications Subject to Limited Sampling Rate-Part II: Spreading - Li, Husheng; Said, Karim; Liu, Lingjia (IEEE International Conference on Communications (2003), 2025)
In integrated sensing and communications (ISAC), which ie expected to be one of the six major technologies in 6G wireless networks, communications may share the large bandwidth used for sensing, due to the waveform sharing between the two tasks. The large bandwidth requires a high sampling rate of analog-to-digital converter (ADC), thus making the hardware implementation difficult. In the second part of this paper, spectrum spreading that has been used in code division multiple access (CDMA) is leveraged to address the sampling rate challenge: the communication signal bandwidth is set to meet the maximum sampling rate of ADC; the corresponding Shannon bandwidth is then spread to the available Fourier bandwidth using spreading codes. At the receiver, matched filter is used for de-spreading the signal, which retrieves sensing information and communication data. The data signal is then sampled and further processed for data retrieval and sensing. The two sensing results are fused for the final decision of sensing in a hierarchical manner. The proposed scheme is demonstrated using numerical simulations.